2012
DOI: 10.1080/02786826.2012.716550
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Solid Particles Behavior in a Heated Cavity at High Rayleigh Numbers

Abstract: Transport and deposition of solid particles in a differentially heated cavity at high Rayleigh numbers up to 10 8 was studied using an Eulerian-Lagrangian computational method. Two-dimensional Navier-Stokes and energy equations were solved and the motions of particles with diameters in the range of 10 nm to 10 µm were simulated. Effects of drag, lift, thermophoresis and Brownian forces on the particle trajectories were investigated. It was observed that the variation of Rayleigh number can significantly change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Bagheri et al [12] numerically simulated the deposition of solid particles with diameters between 10 nm and 10 lm in a differentially heated cavity filled with air. It was reported that the effects of thermophoretic and Brownian force are important on the distribution and deposition of sub-micron particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagheri et al [12] numerically simulated the deposition of solid particles with diameters between 10 nm and 10 lm in a differentially heated cavity filled with air. It was reported that the effects of thermophoretic and Brownian force are important on the distribution and deposition of sub-micron particles.…”
Section: Introductionmentioning
confidence: 99%
“…particle deposition on heat exchanger surfaces can reduce the heat transfer rate and adversely affect the energy efficiency of these equipment [8,9]. Therefore, several studies have been carried out to understand this problem using Eulerian-Lagrangian methods [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As an example in the reference [8] the relationship and formula for C c , F D , F B and etc are described as below. Cunningham'sfactor is…”
Section: Geometry and Boundary Conditionsmentioning
confidence: 99%
“…H. Hassanzadehet al [7] investigated numerically dispersion and removal of microaerosol particles in a horizontal concentric annulus by Lattice Boltzmann Method and Lagrangian Runge-Kutta procedure with the assumption of one-way coupling. G. H. Bagheri et al [8] studied transport and deposition of solid particles in a differentially heated cavity at high Rayleigh numbers up to 10 8 using an Eulerian-Lagrangian computational method. T. H. Kuehn, R. J. Goldstein [9] investigated an experimental and theoretical study of natural convection in the annulus between horizontal concentric cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…At Ra = 104, particles are more uniformly distributed than for the case with Ra = 106. Studies on micrometer-sized particle-laden flow usually show particle separation from the base fluid, e.g., [ 36].…”
Section: Figmentioning
confidence: 99%